"My Father Was Told to Talk to the Environment First Before Anything Else" - Arctic Environmental Education in the Language of the Land - Tommy Akulukjuk; Derek Rasmussen (Hampton Press, 2009)
Chapter examines the importance of Indigenous languages and the connection between ecology and language, focusing on the Nunavut Territory where “the land speaks Inuktitut” . The chapter was constructed from conversations and e-mails between Inuk writer and researcher Tommy Akulukjuk, and independent researcher Derek Rasmussen, who lived in Nunavut for 12 years.